Filamentous fungal endophthalmitis: results of combination therapy with intravitreal amphotericin B and voriconazole - Mithal, Kopal (Clin Ophthalmol, 2015)
PURPOSE: To report outcomes of exogenous fungal endophthalmitis treated with combination of intravitreal antifungal agents. DESIGN: Retrospective, non-randomized, interventional, consecutive case series. METHODS: Twelve eyes of twelve consecutive cases of filamentous fungal endophthalmitis were treated with a combination of intravitreal amphotericin-B and intravitreal voriconazole (AmB-Vo Regime) along with pars plana vitrectomy at a single center. Clinical characteristics, microbiology results, treatment strategy, visual, and anatomical outcomes were analyzed. RESULTS: Ten cases out of the twelve were postoperative endophthalmitis of which nine were part of a post cataract surgery cluster. The remaining included endophthalmitis following keratitis post pterygium excision (1) and following open globe injury (2). The most common fungus was Aspergillus terreus, which was isolated in 8/12, followed by A. flavus in 2/12 and Fusarium solani in 1/12. The presenting visual acuity ranged from light perception (LP) to counting fingers. The visual acuity at final follow-up was 20/400 or better in 7/12 eyes (58.33%) and 20/60 in 2/12 eyes (range 20/60 to LP). All eyes with corneal involvement had final visual acuity 20/400 or worse. Globe salvage was achieved in all cases. CONCLUSION: Combining intravitreal amphotericin-B and voriconazole could be a novel treatment strategy in the management of endophthalmitis caused by filamentous fungus. Eyes with corneal involvement had poor visual outcome either with or without therapeutic penetrating keratoplasty.